A selectivity study of sodium‐dependent glucose cotransporter 2/sodium‐dependent glucose cotransporter 1 inhibitors by molecular modeling. Issue 8 (5th March 2015) - Xu, Jinxing; Yuan, Haoliang; Ran, Ting; Zhang, Yanmin; Liu, Haichun; Lu, Shuai; Xiong, Xiao; Xu, Anyang; Jiang, Yulei; Lu, Tao; Chen, Yadong
<x xml:space="preserve">Abstract</x> Sodium‐dependent glucose cotransporters (SGLTs) play an important role in glucose reabsorption in the kidney and have been identified as promising targets to treat diabetes. Because of the side effects like glucose and galactose malabsorption by targeting SGLT1, highly selective SGLT2 inhibitors are more promising in the treatment of diabetes. To understand the mechanism of selectivity, we conducted selectivity‐based three‐dimensional quantitative structure–activity relationship studies to highlight the structure requirements for highly selective SGLT2 inhibitors. The best comparative molecular field analysis and comparative molecular similarity indices analysis models showed the noncross‐validated coefficient (r2) of 0.967 and 0.943, respectively. The predicted correlation coefficients (r2pred) of 0.974 and 0.938 validated the reliability and predictability of these models. Besides, homology models of SGLT2 and SGLT1 were also constructed to investigate the selective mechanism from structure‐based perspective. Molecular dynamics simulation and binding free energy calculation were performed on the systems of a potent and selective compound interacting with SGLT2 and SGLT1 to compare the different binding modes. The simulation results showed that the stretch of the methylthio group on Met241 had an essential effect on the different binding modes between SGLT1 and SGLT2, which was consistent with the three‐dimensional quantitative structure–activity relationship analysis. Hydrogen bond analysis and binding free energy calculation revealed that SGLT2 binding complex was more stable and favorable than SGLT1 complex, which was highly correlated with the experimental results. Our obtained results give useful information for the investigation of the inhibitors' selectivity between SGLT2 and SGLT1 and will help for further development of highly selective SGLT2 inhibitors. Copyright © 2015 John Wiley & Sons, Ltd.